Bond durability of steel plate to concrete prism using structural adhesives after exposure to 7 years in laboratory environment - Mokhtar, Nor Izzah (Penerbit UTM Press, 2017)
Structural integrity and durability has long been an area of study that is critical in order to ensure structures such as buildings, bridges etc. are safe enough to stand erected for many years. The technique of bonding steel plates to the surface of concrete using epoxy adhesives system has been used on a number of structures throughout the world to enhance load transferring capability. Deterioration in strength of concrete structures due to corrosion of steel can cause premature failure in existing structures or buildings. The objective of this study is to investigate the bond performance of steel to concrete using structural epoxy system. The sample at hand was prepared and left exposed for 7 years under normal ambient laboratory environments. This study focused on the outcome of bond performances of the bonded steel plate to concrete prism under pull out load. The sample (SPECS-7) that used in this study is approximately 7 years old with the steel plates surfaces was corroded and being compared with sample (SPECS-1) tested in 2008. The maximum load and maximum extension recorded at failure by sample SPECS-7 is 76.85kN and 3.04 mm at 181.8s which shows a decrease by 7 kN or 8% and 5.70 mm to 3.04 mm or 46% compared with sample SPECS-1 respectively. The extension comparison with SPEC-1 shows a reduction from 5.70 mm to 3.04 mm which is about 46 % less. There was significant amount of corrosion developed over the years which does not show to have affected the overall performance of the bonded system. Nevertheless, there was on average a small increase in bond strength with time although the controlled sample failed at a marginally lower load.